Infection of eggs of Triatoma dimidiata (Hemiptera; Reduviidae) with Telenomus fariai (Hymenoptera: Scelionidae) in Alajuela, Costa Rica - Rojas Araya, Diana (2023)
Microhymenoptera of the species Telenomus fariai (Hymenoptera: Scelionidae) are recognized parasitoids of eggs of kissing bugs. These wasps constitute a potential modulator of populations of Triatoma dimidiata (Hemiptera: Reduviidae), the main vector of Chagas disease in Central America. This study describes the infection by Telenomus fariai in field-collected eggs of Triatoma dimidiata (Hemiptera: Reduviidae). The eggs were obtained in the peridomicile of a house in Tuetal Sur (Alajuela Province, Costa Rica). The wasp progeny, observed 24 h after receiving the eggs, consisted mainly of females (94.0%). The species confirmation was carried out by analysis of the male genitalia and DNA sequences corresponding to a fragment of the cytochrome c oxidase subunit 1 mitochondrial gene (COI). The identity of the wasp, based on analysis of sequences, places the local strain in proximity to specimens collected in Veracruz, Mexico. The characterization of strains of T. fariai could be useful for the identification of the best candidates to be employed in the biological control of T. dimidiata.